Evaluating the efficacy of biological control of three of three exotic homopteran pests in Tropical Africa - Neuenschwander, Peter (Springer, 1996)
Techniques for evaluating biological control of cassava mealybug (Phenacoccusmanihoti Matile-Ferrero), mango mealybug (Rastrococcus invadens Williams), and spiralling whitefly (Aleurodicus dispersus Russell) are described. In each case, two exotic hymenopterous parasitoids were introduced. Alone or together, they brought the pests under control, while indigenous and exotic coccinelIids played a minor role. Control was achieved in large areas where the exotic parasitoid(s) had been present for more than 2-4 years. The impact was documented by (1) exclusion experiments; (2) long-term population dynamics studies; (3) laboratory and field experiments contributing to simulation models; and, most importantly, (4) quantitative results from large-scale surveys evaluated by multivariate analyses. In many countries, the main introduced parasitoid proved to be the most important factor contributing to the decline of the pest populations, recovery of plant growth and yields. Non-target species were only affected through the reduction in their food sources. The impact was scale-neutral, benefitting subsistence farmers and commercial farmers alike. The population reduction remained stable (in the order of ten times over outbreak levels). In economic terms, excluding ecological and health benefits, both the P. manihoti and R. invadens projects returned benefits to African farmers that amounted to a multiple of the research and implementation costs paid for by development agencies. Sound evaluation of the efficiency of biological control is considered to have been one of the pillars for the ultimate success of these projects.